2012
DOI: 10.1002/sim.4481
|View full text |Cite
|
Sign up to set email alerts
|

Estimating vaccination coverage for the trivalent measles–mumps–rubella vaccine from trivariate serological data

Abstract: The effectiveness of childhood immunization programs depends on the vaccination coverage actually achieved. Routinely collected coverage data are not always available, and comparability between countries is often compromised because of different data collection methods. In 2000, Gay developed a method to estimate trivalent vaccination coverage from readily available trivariate serological data on the basis of parametric assumptions related to the rate of seroconversion for each vaccine component and probabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Following the approach of Gay 16 (unpublished) (described in Altmann and Altmann 17 ) and Goeyvaerts et al . 6 , it can be shown (Supporting Material) that p a,m,r can be expressed in terms of the following factors:The vaccination coverage ( v a ) in age group a during the SIA in 2011, assumed to be identical for all age groups..The proportion of people in age group a who were not vaccinated during the SIA in 2011 who acquired antibodies to infection i (denoted c am and c ar for measles and rubella respectively), assumed to differ between each single year age band. For measles, these people would have become seropositive because of natural infection or vaccination; for rubella, they would have become seropositive because of natural infection.The proportion of people who were negative for antibodies to infection i just before the SIA in 2011, but then became positive for antibodies to infection i because of vaccination, assumed to be identical for all ages (denoted e m and e r for measles and rubella respectively).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the approach of Gay 16 (unpublished) (described in Altmann and Altmann 17 ) and Goeyvaerts et al . 6 , it can be shown (Supporting Material) that p a,m,r can be expressed in terms of the following factors:The vaccination coverage ( v a ) in age group a during the SIA in 2011, assumed to be identical for all age groups..The proportion of people in age group a who were not vaccinated during the SIA in 2011 who acquired antibodies to infection i (denoted c am and c ar for measles and rubella respectively), assumed to differ between each single year age band. For measles, these people would have become seropositive because of natural infection or vaccination; for rubella, they would have become seropositive because of natural infection.The proportion of people who were negative for antibodies to infection i just before the SIA in 2011, but then became positive for antibodies to infection i because of vaccination, assumed to be identical for all ages (denoted e m and e r for measles and rubella respectively).…”
Section: Methodsmentioning
confidence: 99%
“…Such analyses also allow estimation of the vaccination coverage, allowing verification of reported levels of coverage. To our knowledge, the only studies to date which have estimated the immunogenicity using such analyses considered the measles-mumps-rubella (MMR) vaccine in Western countries and found levels of seroconversion of at least 94% for the measles and rubella components 6,7 , even when adjusting for possible waning in seroprevalence following vaccination 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The variability in values for the E and I durations in Table suggests limited agreement about the durations for average exposure and infection periods. The review process also revealed many excluded studies that estimated model inputs, which similarly showed a wide range of assumptions. Hypothetical modeling showed the importance of including the latency period and explored different formulations for seasonality in measles and rubella models .…”
Section: Resultsmentioning
confidence: 99%